Impact of Maize-Legume Intercrops for the Management of Fall Armyworm, Spodoptera frugiperda J. E. Smith (Lepidoptera; Noctuidae) in Chitwan, Nepal - Adhikari, Chiran; Tiwari, Sundar; Thapa, Resham Bahadur; Neupane, Saraswati (Agriculture Development Journal, 2025)
Fall armyworm (Spodoptera frugiperda J. E. Smith, 1797) is an invasive, polyphagous, voracious, and destructive pest that threatens maize production globally, including in Nepal. This study aimed to evaluate suitable maize intercropping systems and assess their impact on fall armyworm damage, the abundance of natural enemies, and maize grain yield. Field experiments were conducted in 2022 on spring maize in Chitwan, Nepal. The study employed a Randomized Complete Block Design (RCBD) with six treatments, each replicated four times. The treatments included maize intercropped with rajma bean (Phaseolus vulgaris L.), mungbean (Vigna radiata L.), cowpea (Vigna unguiculata L.), soybean (Glycine max L.), and black gram (Vigna mungo L.), along with a maize monoculture as the control. Data on fall armyworm damage were collected at 10-day intervals starting from 21 days after maize sowing. Visual observations were made to count the total number of crop stands, infected plants, live larvae, and the number of predators and parasitoids. The results showed that maize-soybean intercropping had the lowest fall armyworm infestation on maize, followed by maize with black gram and maize with mungbean. In contrast, mono-cropped maize had the highest percentage of plant infestation. The abundance of beneficial insects was higher in legume-intercropped maize fields. Additionally, among the intercropping combinations, the yield of maize-mungbean intercropped was higher (8.09 mt/ha) than that of mono-cropped maize (6.24 mt/ha). Therefore, intercropping with legumes could be an effective and sustainable management strategy to control fall armyworm, increase beneficial arthropod diversity, and boost maize yield.